HUMAN IMPACTS HAVE SHAPED HISTORICAL AND RECENT EVOLUTION IN AEDES AEGYPTI, THE DENGUE AND YELLOW FEVER MOSQUITO. (23rd October 2013) - Brown, Julia E.; Evans, Benjamin R.; Zheng, Wei; Obas, Vanessa; Barrera‐Martinez, Laura; Egizi, Andrea; Zhao, Hongyu; Caccone, Adalgisa; Powell, Jeffrey R.
<x xml:space="preserve">Abstract</x> Although anthropogenic impacts are often considered harmful to species, human modifications to the landscape can actually create novel niches to which other species can adapt. These "domestication" processes are especially important in the context of arthropod disease vectors, where ecological overlap of vector and human populations may lead to epidemics. Here, we present results of a global genetic study of one such species, the dengue and yellow fever mosquito, Aedes aegypti, whose evolutionary history and current distribution have been profoundly shaped by humans. We used DNA sequences of four nuclear genes and 1504 single nucleotide polymorphism (SNP) markers developed with restriction‐site associated DNA (RAD) sequencing to test the hypothesis that Ae. aegypti originated in Africa, where a domestic form arose and spread throughout the tropical and subtropical world with human trade and movement. Results confirmed African ancestry of the species, and supported a single subspeciation event leading to the pantropical domestic form. In addition, genetic data strongly supported the hypothesis that human trade routes first moved domestic Ae. aegypti out of Africa into the New World, followed by a later invasion from the New World into Southeast Asia and the Pacific. These patterns of domestication and invasion are relevant to many species worldwide, as anthropogenic forces increasingly impact evolutionary processes.